2022
DOI: 10.1097/rli.0000000000000943
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Breath-Hold Fat-Suppressed T2-Weighted Images With Deep Learning–Based Reconstruction of the Liver

Abstract: Objectives: The aim of this study was to evaluate the usefulness of breath-hold turbo spin echo with deep learning-based reconstruction (BH-DL-TSE) in acquiring fat-suppressed T2-weighted images (FS-T2WI) of the liver by comparing this method with conventional free-breathing turbo spin echo (FB-TSE) and breath-hold half Fourier single-shot turbo spin echo with deep learning-based reconstruction (BH-DL-HASTE). Materials and Methods: The study cohort comprised 111 patients with suspected liver disease who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…14 Deep learning (DL) reconstruction was recently implemented in body MRI, and studies have reported shortened acquisition times and better image quality using DL-reconstructed T2-weighted imaging compared with conventional turbo spin echo (TSE) or half-Fourier acquisition single-shot TSE (HASTE) T2-weighted imaging. [15][16][17][18] Fewer studies have applied DL-reconstructed DWI (DL-DWI) in body imaging, likewise revealing reduced scan time and improved image quality in evaluating the liver, breast, and prostate gland. [19][20][21][22] Currently, analyses of the impact of strategies to compensate respiratory artifacts on image quality, focal lesion detection, and scan time in liver DL-DWI are lacking.…”
mentioning
confidence: 99%
“…14 Deep learning (DL) reconstruction was recently implemented in body MRI, and studies have reported shortened acquisition times and better image quality using DL-reconstructed T2-weighted imaging compared with conventional turbo spin echo (TSE) or half-Fourier acquisition single-shot TSE (HASTE) T2-weighted imaging. [15][16][17][18] Fewer studies have applied DL-reconstructed DWI (DL-DWI) in body imaging, likewise revealing reduced scan time and improved image quality in evaluating the liver, breast, and prostate gland. [19][20][21][22] Currently, analyses of the impact of strategies to compensate respiratory artifacts on image quality, focal lesion detection, and scan time in liver DL-DWI are lacking.…”
mentioning
confidence: 99%
“…10 Deep learning reconstruction (DLR), which uses a deep convolutional neural network trained to reconstruct images with higher quality, can improve the signal-to-noise ratio (SNR), sharpness, and spatial resolution of MRI and has been used effectively in various diseases. [15][16][17][18][19][20][21][22] In rectal MRI, the usefulness of DLR in predicting pathological complete response after neoadjuvant treatment has been reported. 16 However, the value of DLR in assessing local tumor extent has not been reported, and the impact of DLR on radiologists' judgments remains to be elucidated despite the direct impact of MRI-positive diagnoses on patient management.…”
mentioning
confidence: 99%
“…Deep learning reconstruction (DLR), which uses a deep convolutional neural network trained to reconstruct images with higher quality, can improve the signal-to-noise ratio (SNR), sharpness, and spatial resolution of MRI and has been used effectively in various diseases 15–22 . In rectal MRI, the usefulness of DLR in predicting pathological complete response after neoadjuvant treatment has been reported 16 .…”
mentioning
confidence: 99%